BULK FILL COMPOSITE RESIN RESTORATION TECHNIQUES REPLACE INCREMENTAL TECHNIQUES : TEKNIK RESTORASI RESIN KOMPOSIT BULK FILL MENGGANTIKAN TEHNIK INKREMENTAL - Ilma Yudistian (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2021)
Introduction: Shrinkage during the polymerization process is the main disadvantage of using composite resins because it creates pressure between the tooth and the restoration which causes failure of the adhesion of the composite resin to the tooth, micro-fissures, and cuspid deflection. Review: To reduce shrinkage that occurs, it is known that conventional composite resins must be inserted into the cavity incrementally or in layers with a maximum thickness of 2 mm per layer. However, the incremental insertion method has several disadvantages, namely that it requires a longer clinical time for restoration. To overcome the shortcomings of these conventional composites, Bulk-fill composite resin was introduced. Composite bulk fill is a sophisticated technology that allows composites to be directly placed on the restoration, has a low polymerization shrinkage to reduce micro-leakage, reduces stress in the presence of elasticity, increases the depth of at least 4 mm translucent at the time of application, is very conducive to light transmission, is more flowable to allow adaptation to the cavity, including cervical margins, it is easy to apply with minimal handling and is resistant to large stresses. Conclusion: With the characteristics possessed by the Bulk-fill composite resin, it is known that the bulk-fill technique in addition to reducing the clinical application time, can also improve the edge adaptation between the restoration and the tooth compared to the incremental technique, without reducing its physical strength.